2007
DOI: 10.2967/jnumed.106.037085
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Radiolabeled Gastrin Analogs for Peptide Receptor-Targeted Radionuclide Therapy

Abstract: The gastrin/cholecystokinin-2 (CCK-2) receptor has been identified as a possible target for peptide receptor radionuclide imaging and therapy. Several radiolabeled peptides binding to this receptor have been explored in animal models and clinical trials but either low tumor uptake or high renal retention has been found. The aim of this study was to identify a peptide with improved tumor-to-kidney pharmacodynamics when compared with current candidates. Methods: A small peptide-chelator library of 34 compounds b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 17 publications
(20 reference statements)
4
82
0
Order By: Relevance
“…In comparison with other studies performed with 111 In-labeled MG0 on BALB/c mice, bearing various tumor types, the highest tumor uptake was found in the CCK2/gastrin receptor transfected cell lines (6.1 and 13%IA/g vs. 0.79%IA/g for GOT2 after 1 h) (31,32,50) (Table IV). The uptake in the rat endocrine pancreatic tumor model AR42J was higher than in GOT2, but lower than in the transfected tumors (50).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In comparison with other studies performed with 111 In-labeled MG0 on BALB/c mice, bearing various tumor types, the highest tumor uptake was found in the CCK2/gastrin receptor transfected cell lines (6.1 and 13%IA/g vs. 0.79%IA/g for GOT2 after 1 h) (31,32,50) (Table IV). The uptake in the rat endocrine pancreatic tumor model AR42J was higher than in GOT2, but lower than in the transfected tumors (50).…”
Section: Discussionmentioning
confidence: 91%
“…The uptake in the rat endocrine pancreatic tumor model AR42J was higher than in GOT2, but lower than in the transfected tumors (50).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the anionic Nterminal pentaglutamic acid sequence of minigastrin analogs, or replacement by a histidine-histidine-glutamic acid sequence, resulted in a marked decrease in kidney uptake. Again this was accompanied by a decrease in tumor uptake but an increased tumor-to-kidney ratio (48). Replacing minigastrin's pentaglutamic acid sequence by a neutral pentaglutamine sequence reduced uptake in tumors and organs positive for the cholecystokinin 2 receptor more than it reduced renal uptake (3).…”
Section: Reduction Of Renal Uptakementioning
confidence: 98%
“…In an acidic environment, however, such as occurs within the lysosomal compartment, the net negative charge of the peptide will be reduced and this may affect intracellular metabolism. In a previous study, we found that the insertion of histidine can also enhance the performance of indium- 1,4,7,10-tetraazacyclododecane-N,N9,N$,N9$-tetraacetic acidlabeled peptides (17), and this phenomenon is therefore worthy of further investigation. Two other groups have explored the use of 99m Tc-labeled minigastrin analogs in the nude mouse AR42J xenograft model.…”
Section: Side-chain Coordination In Hynic Peptides • King Et Almentioning
confidence: 99%
“…Von Guggenberg et al have compared the biodistribution of peptides labeled using both the HYNIC and the tricarbonyl labeling systems (18,19), and Nock et al have studied that of a tetraamine conjugate (20). However, most of these studies used peptides containing the gastrin pentaglutamate motif, which results in moderate increases in tumor uptake but high renal retention, compared with the truncated sequence studied herein (17). In our experience, caution should, in any case, be exercised in directly comparing results from different centers-even when apparently the same tumor cell line is used-because of differences in levels of receptor expression observed in different laboratories.…”
Section: Side-chain Coordination In Hynic Peptides • King Et Almentioning
confidence: 99%